ON THE ROLE OF REGIONAL UNIVERSITIES IN THE DEVELOPMENT OF SCIENCE AND EDUCATION - Georgy V. Dedkov; Arthur A. Kyasov; Khasbi B. Kushkhov (Высшее образование в России)
We discuss the role of regional universities in the development of physical-chemical research and education on the example of Kabardino-Balkarian State University (KBSU). Special attention is paid to the development of scientific schools in physics and chemistry. The authors dwell on the prehistory of the development of natural sciences in KBSU during the Soviet period and the most important achievements of the past two decades in such fields as fluctuational electrodynamics, electrochemistry, nanochemistry, high molecular chemistry.